2010
DOI: 10.1099/vir.0.026443-0
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in the duck intestine following infection with low-pathogenic avian influenza viruses or stimulation with a Toll-like receptor 7 agonist administered orally

Abstract: This study analysed the immune response in the intestinal tract of ducks infected with low-pathogenic avian influenza viruses compared with ducks treated orally with R848, a synthetic Toll-like receptor 7 (TLR7) agonist. Influenza virus infection induced a type I interferon (IFN)-dependent immune response characterized by the expression of Mx transcripts in the ileum at levels that were proportional to viral load. Mx transcripts were detected in differentiated enterocytes from influenza virus-infected ducks. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
3
19
1
Order By: Relevance
“…This was accompanied by a moderate antibody response. These data are in agreement with previous studies performed in mallard ducks [3], [4] or when cross-immunity between H3N8 and H4N6 was compared in mallards, quails and pheasants [14]. The mechanisms sustaining this protection and the duration of this protective immunity still need to be elucidated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was accompanied by a moderate antibody response. These data are in agreement with previous studies performed in mallard ducks [3], [4] or when cross-immunity between H3N8 and H4N6 was compared in mallards, quails and pheasants [14]. The mechanisms sustaining this protection and the duration of this protective immunity still need to be elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…Among aquatic birds, mallards ( Anas platyrhynchos ) and their domestic counterparts Pekin ducks ( Anas platyrhynchos domesticus ), are of particular epidemiological importance [2]. In ducks, LPAIV infections are mainly asymptomatic and restricted to the epithelial cells lining the distal digestive tract [3]. The subsequent release of virus in feces is therefore a main source of contamination for the environment [4].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Daoust et al (2011) correspond with those for experimental LPAIV infection in domestic ducks by Slemons & Easterday (1978) and Kida et al (1980), who found virus replication primarily in the epithelium of cloacal bursa and the large intestine. However, they do not correspond with the results of the study of Volmer et al (2010), who found virus replication more frequently in the small intestine than in the large intestine of domestic ducks experimentally infected with a genetically engineered virus possessing both human-type and avian-type amino acid motifs in the NS1 protein.…”
Section: Discussioncontrasting
confidence: 96%
“…was detected in the lung (Rebel et al, 2011), although high levels of the IFN-inducible genes Mx and PKR were found in the lung of H5N1-infected chickens (Daviet et al, 2009). The production of cytokines after a virus infection is mediated by pathogen recognition receptors (PRRs), including Toll-like receptors (TLRs) and RIG-I-like receptors (Kawai & Akira, 2008;Diebold, 2009) Induction of these receptors has been studied in lowpathogenic avian influenza infections in both chickens and ducks (Volmer et al, 2011;Karpala et al, 2011b;Cornelissen et al, 2012;Liniger et al, 2012). Barber et al (2010) reported the absence of RIG-I in chickens and suggested that the severity of HPAI infection in chickens may be explained by the absence of RIG-I activity.…”
Section: Introductionmentioning
confidence: 99%